2019
DOI: 10.1016/j.immuni.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the Full-Length Murine and Human Gasdermin D Reveal Mechanisms of Autoinhibition, Lipid Binding, and Oligomerization

Abstract: Gasdermin D (GSDMD) is an effector molecule for pyroptosis downstream of canonical and noncanonical inflammasome signaling pathways. Cleavage of GSDMD by inflammatory caspases triggers the oligomerization and lipid binding by its N-terminal domain, which assembles membrane pores, whereas its C-terminal domain binds the N-terminal domain to inhibit pyroptosis. Despite recent progress in our understanding of the structure and function of the murine gasdermin A3 (mGSDMA3), the molecular mechanisms of GSDMD activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(215 citation statements)
references
References 34 publications
(70 reference statements)
4
198
0
Order By: Relevance
“…In 2018, the crystal structure of the mouse GSDMA3 pore was solved (Ruan et al, 2018), providing critical insight into GSDM pore formation. Although the C-terminal domain of GSDMD, as well as the full-length GSDMA3, had previously been solved (Ding et al, 2016; Kuang et al, 2017; Liu et al, 2018) and later the full-length mouse and human GSDMD (Liu et al, 2019), this was the first crystal structure giving insights into the molecular basis of pore formation. It revealed that GSDMA forms pores consisting of 27–28 protomers with an internal diameter of ∼180 Å.…”
Section: Gasdermins the Pore-forming Effectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, the crystal structure of the mouse GSDMA3 pore was solved (Ruan et al, 2018), providing critical insight into GSDM pore formation. Although the C-terminal domain of GSDMD, as well as the full-length GSDMA3, had previously been solved (Ding et al, 2016; Kuang et al, 2017; Liu et al, 2018) and later the full-length mouse and human GSDMD (Liu et al, 2019), this was the first crystal structure giving insights into the molecular basis of pore formation. It revealed that GSDMA forms pores consisting of 27–28 protomers with an internal diameter of ∼180 Å.…”
Section: Gasdermins the Pore-forming Effectorsmentioning
confidence: 99%
“…Interestingly, however, in the crystal structure of both GSDMA3 and GSDMD, no cysteine–cysteine disulfide bonds were observed. Modeling of the GSDMD pore based on the GSDMD structure and GSDMA3 pore structure has identified three possible interfaces important for oligomerization (Ruan et al, 2018; Liu et al, 2019). Mutations of residues in these interfaces blocked oligomerization and pyroptosis.…”
Section: Structural Insights On Gsdmdmentioning
confidence: 99%
“…In the autoinhibited state, GSDM-CT folds back onto GSDM-NT to repress its activity. The basis for this autoinhibitory mechanism was elucidated by the X-ray crystal structures of full-length (FL) mouse GSDMA3 as well as both human and mouse GSDMD (Ding et al 2016;Kuang et al 2017;Liu et al 2018Liu et al , 2019. GSDM-NT contains both α-helices and extended β-strands, whereas GSDM-CT is almost exclusively α-helical.…”
Section: Mechanism Of Gsdm Autoinhibitionmentioning
confidence: 99%
“…Functional assays further indicated that this domain interface is critical for the autoinhibition of GSDMD. 4 Previous studies found that GSDMD can be cleaved by active caspase-1 downstream of canonical inflammasome complexes, including NLRC4 inflammasome sensing of bacterial flagellin, NLRP3 inflammasome sensing of reactive oxygen species (ROS) and K + and AIM2 inflammasome sensing of viral DNA. 6 Additionally, GSDMD can also be cleaved by active caspase-11 (caspase-4/5 in humans) downstream of lipopolysaccharide (LPS)-activated non-canonical inflammasome complexes.…”
Section: The Members Of Gasdermin Family Gsdmdmentioning
confidence: 99%
“…In healthy cells, however, the cytotoxic effects mediated through the N-terminal domain can be suppressed by the autoinhibitory C-terminal domain. [2][3][4] In this review, we highlight recent advances in understanding the activation mechanism of the gasdermin. Moreover, we also focus on their roles in host immunity and autoinflammation diseases.…”
Section: Introductionmentioning
confidence: 99%